THEME-RHEME ORGANIZATION IN TURKISH A FUNCTIONAL-PRAGMATIC APPROACH - Mohammad Jafar Jabbari; Ali Kazemi; Reza Kafipour (European Scientific Journal, ESJ, 2012)
Turkish does not tend to use passive sentences much less than English and some other European Languages. Passive is used when the doer of the action is not present in the sentence for any reason. On the other hand, in Turkish, unlike English and many other European languages, case is assigned to noun phrases (NPs) overtly and by affixation. This article aims to find the correlation between case assignment type and passive formation, to explain why Turkish does not tend to form agentive passive sentences, and to introduce a non-passive alternative for agentive passive sentences, within the framework of Functional Sentence Perspective (FSP).